[Budget impact analysis of idarucizumab for the management of patients treated with dabigatran in emergency / urgent situations in Italy] - Belisari, Andrea; Iannazzo, Sergio; Di Pasquale, Giuseppe; Fresco, Claudio; Mantovani, Lorenzo Giovanni; Ruggeri, Maria Pia; Toni, Danilo; Landolfi, Raffaele (Farmeconomia. Health economics and therapeutic pathways, 2016)
BACKGROUND: Each drug therapy with an anticoagulant effect may require, in emergency conditions, a rapid and specific strategy for a prompt restoration of coagulation. Dabigatran is the first-in-class of the so-called new oral anticoagulants (NAO), that have been made available in recent years in addition to traditionally-used vitamin K antagonists (VKA). Idarucizumab is a monoclonal antibody that binds to dabigatran, neutralizing its anticoagulant effect. OBJECTIVE: To assess the economic effect of idarucizumab in patients treated with dabigatran when the rapid reversal of its anticoagulant effect is required. METHODS: The analysis was carried over through the development of a budget impact model specifically adapted to the context of Italian care. The analysis was conducted along a time horizon of five years. The target population was defined by those patients on dabigatran treatment presenting uncontrolled and life-threatening bleedings (gastro-intestinal, intracranial or other) or requiring emergency surgery or urgent procedures. The estimation of healthcare resources (i.e. diagnostic procedures, medications, and other in-hospital services) needed for the management of uncontrolled bleeding and emergency surgery in patients treated with dabigatran was obtained from a panel of five Italian Clinical Experts. Unit costs were derived from current prices and tariffs. RESULTS: The total cost of management with the current therapeutic modalities ranged from € 16.5 million in year 1 to € 20.1 million in year 5. In the scenario with idarucizumab the total cost ranged from € 15.4 million in year 1 to € 18.7 million in year 5. The adoption of idarucizumab resulted in a cumulative 5-year savings of 6.5 million euro corresponding to 7.1% of the total expense. CONCLUSION: Idarucizumab for the management of patients treated with dabigatran in emergency / urgent situations has the potential for substantial savings, compared to treatments currently available. This preliminary assessment will require further confirmatory evidence when the product will become available in Italian healthcare setting. [Article in Italian]